Evaluation of Cerebral Blood Flow and Metabolic Function With Methods of Nuclear Medicine in Chronic Liver Disease - Erdoğan, Serpil (Fırat University, 2003)
Hepatic encephalopathy is the most crucial neuropsychiatric complication of chronic liver disease. Various precipitating factors such as dietary protein intake, gastrointestinal haemorrhage and sedatives play a part in the development of hepatic encephalopathy. Nuclear medicine techniques for the evaluation of cerebral blood flow and metabolic functions of patients with kronic liver disease were summarized in this review.

Hepatik ensefalopati sirozun en önemli nöropsikiyatrik komplikasyonudur. Hepatik ensefalopatiyi hazırlayıcı birçok faktör vardır. En sıklıkla görülenler, oral olarak fazla protein alımı, gastrointestinal kanamalar ve sedatiflerin kullanımıdır. Bu derlemede kronik karaciğer hastalığında beyin kan akımı ve metabolizma değişikliklerinin değerlendirilmesinde nükleer tıp teknikleri özetlenmiştir.
Kronik Karaciğer Hastalığında Beyin Kan Akımı ve Metabolik Fonksiyonlarının Nükleer Tıp Yöntemleri ile Değerlendirilmesi